2011
DOI: 10.1038/ncomms1338
|View full text |Cite
|
Sign up to set email alerts
|

Determination of nanoparticle size distribution together with density or molecular weight by 2D analytical ultracentrifugation

Abstract: Nanoparticles are finding many research and industrial applications, yet their characterization remains a challenge. Their cores are often polydisperse and coated by a stabilizing shell that varies in size and composition. No single technique can characterize both the size distribution and the nature of the shell. Advances in analytical ultracentrifugation allow for the extraction of the sedimentation (s) and diffusion coefficients (D). Here we report an approach to transform the s and D distributions of nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
235
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(246 citation statements)
references
References 52 publications
9
235
0
2
Order By: Relevance
“…The composition and structure of the ligand shell were the only physical characteristics varied between the particles. Figure 1 illustrates that the size distributions of the NPs showed negligible differences by analytical ultracentrifugation [34]. Since the sedimentation coefficient is dependent chiefly on the size and shape of the NP (the latter being constant for spherical NPs, as exhibited by the frictional ratio plotted on the y axis), we can affirm that the size range between NP types is very similar.…”
Section: Resultssupporting
confidence: 55%
“…The composition and structure of the ligand shell were the only physical characteristics varied between the particles. Figure 1 illustrates that the size distributions of the NPs showed negligible differences by analytical ultracentrifugation [34]. Since the sedimentation coefficient is dependent chiefly on the size and shape of the NP (the latter being constant for spherical NPs, as exhibited by the frictional ratio plotted on the y axis), we can affirm that the size range between NP types is very similar.…”
Section: Resultssupporting
confidence: 55%
“…In the next step, we calculated the core diameters x c and ligand shell thicknesses d shell for the feed and fractions #1 and #2 based on a mass conservation approach presented by Carney et al 51 The results in Table 2 show that d shell was found to be about 1 nm for feed and coarse fraction #1 whereas a slightly smaller value of 0.92 nm was obtained for fraction #2. Table 2 Summary of the data derived from the 2-dimensional AUC analysis of the feed sample, the coarse fraction #1, the fines fraction #2 as well as the residuals fraction #3.…”
Section: Investigation Of the Fractions Via Analytical Ultracentrifugmentioning
confidence: 99%
“…A possibility to determine the particle size and density in just one AUC experiment is the multidimensional approach of simultaneously fitting the sedimentation and diffusion coefficients. 51,52 For this, the frictional ratio which is the hydrodynamic diameter divided by the volume equivalent diameter has to be equal 1. For the CuInS 2 QDs investigated in this study this is a fair assumption since they are spherical in good approximation as shown by the TEM data of Fig.…”
Section: Investigation Of the Fractions Via Analytical Ultracentrifugmentioning
confidence: 99%
“…The diameters of the NPs in the exposure media were quantified by at least one of the following analytical techniques: analytical ultracentrifugation (AUC) (21), fluorescence correlation spectroscopy (FCS) (18,22), and atomic force microscopy (AFM) (23). The size characterization of the NPs was performed under the exact same conditions as the bioaccumulation experiments, including preequilibration of the dispersions for 24 h. Details on the experimental sizing protocols are provided in the supplemental material.…”
Section: Methodsmentioning
confidence: 99%